Islamic Education Methodology In An Indisciplinary Perspective - Khoirun Nisa'; Anis Trianawati (SCHOOLAR: Social and Literature Study in Education, 2024)
As the age of religion progresses, it must be able to be examined academically and serve more than just as an assertion of doctrine. As previously stated, the phenomenon of human diversity must also be viewed from the historical perspective of how individuals and groups have understood and interpreted the norms of the religious teachings they adhere to, in addition to how normative the teachings of revelation are. The purpose of this work is to establish the technique for interdisciplinary Islamic studies as well as comprehend Islam in Indonesia. This study combined a library research strategy with descriptive qualitative methods. According to the study's findings, Indonesian Muslims think and understand Islam according to three different patterns. The text is the first. Religion is comprehended and used in accordance with the text's lafdhiyah (literal sound), or "pure" understanding. The phrase "moderate" refers to academics who create their own, but there is a legal basis. This is the second pattern. The third example is the liberal Muslim, who practices their faith in accordance with the situation. A problem-solving strategy involving an integrated evaluation of several related scientific views is known as an interdisciplinary approach. The study employing several methods or perspectives is the interdisciplinary approach being discussed here. Using simultaneously philosophical, social, historical, and normative perspectives, for instance, in research